DETERMINAN FINANCIAL RISK DISCLOSURE: STUDI PADA PERUSAHAAN YANG TERDAFTAR DALAM MORGAN STANLEY CAPITAL INTERNATIONAL (MSCI) INDONESIA INDEXPERIODE 2014-2016 - Meilani, Sayekti Endah; Wiyadi, W (Jurnal Manajemen Dayasaing, 2017)
The purpose of this study is to examine the effect of corporate characteristics on financial risk disclosure in Indonesia at 2014-2016. The characteristics of the company in this study include firm size, industry type, auditor reputation, ownership concentration, profitability and leverage. Disclosure of financial risk refers to the research of Wibowo and Probohudono (2017) adapted from research by Atanasovski et al (2015), Oorschot (2010), and International Financial Reporting Standard (IFRS) No. 7 on financial instrument: disclosure. The introduction of IFRS 7 by the International Accounting Standards Board can improve the quality of financial risk disclosure practices that all financial reporting authors should undertake. The sample of this study is a company listed on MSCI (Morgan Stanley Capital International) Indonesia Index 2014-2016. The results of this study indicate that information about credit risk and liquidity is the most information disclosed by the company, while information on market risk is not much disclosed. In addition, the results of the study also concluded that firm size, type of industry and profitability variables influence the disclosure of financial risk. Other independent variables such as ownership and leverage concentration have no effect on the level of financial risk disclosure.